Embodying legal precarity: Living with ongoing short-term protection in Germany - Magdalena Suerbaum (International Migration, 2021)
Immigration regimes pay particular attention to the migrant's body in the process of legal and bureaucratic inscription. Legal precarity, defined by the repeated reception of short-term protection from deportation, is an existential and deeply embodied experience. The analysis of Schwangerschaftsduldung (temporary suspension of deportation based on pregnancy) and protection for unaccompanied minors, two legal situations in Germany, can shed light on how the migrant's body receives centre stage in the process of legal status determination and shows how the long journey to relative legal stability deeply affects the body. The two legal categories have in common a temporal limitation and an association with bodily transformations. By centring on the legal trajectories of three migrants, this article shows how the body is taken as the marker of vulnerability and (un)deservingness and becomes the bearer of legal precarity.
Keywords: 300